Field evolved resistance to pyrethroids, neonicotinoids, organophosphates and macrolides in Rhopalosiphum padi (Linnaeus) and Sitobion avenae (Fabricius) from China. (April 2021) - Gong, Peipan; Li, Xinan; Gao, Haifeng; Wang, Chao; Li, Mengyi; Zhang, Yunhui; Li, Xiangrui; Liu, Enliang; Zhu, Xun
Abstract: Rhopalosiphum padi (Linnaeus) and Sitobion avenae (Fabricius) are the predominant pests coexisting on wheat plants. In this study, the susceptibilities of 29 R. padi and 30 S. avenae populations from 15 provinces in China to pyrethroids (beta-cypermethrin and bifenthrin), neonicotinoids (imidacloprid and thiamethoxam), organophosphates (omethoate and chlorpyrifos) and macrolides (avermectin) were determined during 2018–2019. The median lethal insecticide concentrations (LC50 ) indicated that R. padi was more sensitive than S. avenae to most of the insecticides. Monitor results showed that most wheat aphid populations were moderately resistant to pyrethroids. Two R. padi populations were highly resistant to beta-cypermethrin with 127.3-fold and 442.8-fold resistance ratio (RR), and two were highly resistant to bifenthrin (RR of 293.9 and 320.6, respectively). One S. avenae population was highly resistant to beta-cypermethrin (RR of 136.8) and one was highly resistant to bifenthrin (RR of 313.4). All populations of two wheat aphids exhibited low to moderate resistance to neonicotinoids (RR < 100). But over half populations were sensitive or exhibited low resistance to organophosphates and macrolides. The pair-wise correlation coefficients for the insecticide LC50 revealed a positive correlation between beta-cypermethrin and bifenthrin resistance, as well as between the resistance to bifenthrin and omethoate for the two-aphid species. Similarly, significant correlations were detected between the resistance to beta-cypermethrin and avermectin for R. padi . These results may be relevant for developing effective insecticide management strategies that prevent or delay the development of resistance among wheat aphids. Graphical abstract: Image 1 Highlights: Insecticide resistance of R. padi and S. avenae field populations from 15 provinces in China was monitored in 2018–2019. Very high resistance to pyrethroids were found in some populations of two-aphid species. Some wheat aphid populations exhibited low to moderate resistance to neonicotinoids. Most wheat aphid populations were sensitive or exhibited low resistance to organophosphates and macrolides.